Use of intraoperative haemostatic checklists on blood management in patients undergoing cardiac surgery: a scoping review protocol. Issue 8 (24th August 2022) - Irabor, Biobelemoye Ebehireme; Kothari, Asha; Hong, Jonathan; Burnette-Chiang, Bronte; Kent, David; Duhamel, Todd; Arora, Rakesh C
Abstract : Introduction: A major complication of cardiac surgery is bleeding which can require surgical re-exploration and the transfusion of allogeneic blood products. Re-operative procedures for bleeding have been associated with higher rates of mortality and morbidity, therefore an intervention to reduce this complication would be important. Previous investigation has demonstrated that low-cost solutions, such as the use of an intraoperative haemostatic checklist may result in the reduction of bleeding and subsequent transfusion. The goals of this scoping review aim to assess the efficacy of the use of intraoperative haemostatic checklists on blood management in patients undergoing cardiac surgery. Specifically, the objective is to understand if the use of intraoperative haemostatic checklists has been associated with a reduction in bleeding and blood product utilisation in patients undergoing non-emergent cardiac surgery. Methods and analysis: A scoping review of literature identifying randomised control and observational trials, reporting on haemostatic checklists in cardiac surgery, will be undertaken. The proposed review will be guided by the methodological framework proposed by Arksey and O'Malley. A search will be conducted for published and unpublished (grey) literature. Published literature will be searched in the following electronic databases: Scopus, MEDLINE, EMBASE and the Cochrane Library. Relevant grey literature will be identified through conference abstracts. Outcomes chosen are patient centred to ensure reduced bleeding and overall positive experience that reduces complications intraoperatively. Ethics and dissemination: This study does not require ethical approval as the data used are from available publications. Our dissemination strategy includes peer-review publication, presentation at conferences and relevant stakeholders.